Employing 2D‐Perovskite as an Electron Blocking Layer in Highly Efficient (18.5%) Perovskite Solar Cells with Printable Low Temperature Carbon Electrode. Issue 21 (16th April 2022) - Zouhair, Salma; Yoo, So‐Min; Bogachuk, Dmitry; Herterich, Jan Philipp; Lim, Jaekeun; Kanda, Hiroyuki; Son, Byoungchul; Yun, Hyung Joong; Würfel, Uli; Chahboun, Adil; Nazeeruddin, Mohammad Khaja; Hinsch, Andreas; et al.
Abstract: Interface engineering and passivating contacts are key enablers to reach the highest efficiencies in photovoltaic devices. While printed carbon–graphite back electrodes for hole‐transporting material (HTM)‐free perovskite solar cells (PSCs) are appealing for fast commercialization of PSCs due to low processing costs and extraordinary stability, this device architecture so far suffers from severe performance losses at the back electrode interface. Herein, a 2D perovskite passivation layer as an electron blocking layer (EBL) at this interface to substantially reduce interfacial recombination losses is introduced. The formation of the 2D perovskite EBL is confirmed through X‐ray diffraction, photoemission spectroscopy, and an advanced spectrally resolved photoluminescence microscopy mapping technique. Reduced losses that lead to an enhanced fill factor and V OC are quantified by electrochemical impedance spectroscopy and J SC – V OC measurements. This enables reaching one of the highest reported efficiencies of 18.5% for HTM‐free PSCs using 2D perovskite as an EBL with a significantly improved device stability. Abstract : A 2D perovskite passivation layer is introduced as an electron blocking layer at the 3D perovskite/carbon interface in hole transporting layer (HTL) free carbon electrode‐based perovskite solar cells. The substantial reduction of recombination losses due to the electron‐blocking 2D perovskite results in a high power conversion efficiency for HTL‐free devices (18.5%) with an improved stability.